Assessment of microplastic toxicity to embryonic development of the sea urchin Lytechinus variegatus (Echinodermata: Echinoidea). Issue 1 (15th March 2015) - Nobre, C.R.; Santana, M.F.M.; Maluf, A.; Cortez, F.S.; Cesar, A.; Pereira, C.D.S.; Turra, A.
Highlights: Plastic pellets act as a vector of additives and organic pollutants to the water column and interstitial water. Leached chemicals from pellets reduce viability of sea urchin larvae. Newly released pellets have higher toxicity than beach-stranded pellets. The toxicity of stranded pellets depends on the exposure pathway (simulated leaching to interstitial water > water column). Abstract: Apart from the physiological impacts on marine organisms caused by ingesting microplastics, the toxicity caused by substances leaching from these particles into the environment requires investigation. To understand this potential risk, we evaluated the toxicity of virgin (raw) and beach-stranded plastic pellets to the development of embryos of Lytechinus variegatus, simulating transfers of chemical compounds to interstitial water and water column by assays of pellet–water interface and elutriate, respectively. Both assays showed that virgin pellets had toxic effects, increasing anomalous embryonic development by 58.1% and 66.5%, respectively. The toxicity of stranded pellets was lower than virgin pellets, and was observed only for pellet–water interface assay. These results show that (i) plastic pellets act as a vector of pollutants, especially for plastic additives found on virgin particles; and that (ii) the toxicity of leached chemicals from pellets depends on the exposure pathway and on the environmental compartment in which pellets accumulate.